A simple analytical method for determining interlaminar shear stresses in symmetric laminates. (June 2020) - Romera, Jesús María; Carbajal, Neftalí; Mujika, Faustino
Abstract: An analytical procedure for the analysis of interlaminar shear stresses in symmetric laminates is presented. The approach is based on the fact that the coupling effects of each part of the laminate are compensated by the adjacent parts. In a first step, a half of the laminate is considered for determining forces and moments per unit length that prevent the global deformation of the whole laminate. These forces and moments are obtained by solving a homogeneous second order differential equation. Then, the interlaminar shear stresses are computed by applying the stress equilibrium equations and by imposing the continuity of the stresses in the layer interfaces. The analytical results are checked by means of Finite Element Method in the case of quasi-isotropic laminates.